The syntax of Object Marking in Tukano: a formal approach - Braulio Brandão de Oliveira Lopes (2021)
The present research will investigate the syntax of object marking in Tukano. The goal is twofold: (i) to help cover the present gap in minority language description, specifically pertaining to Tukano; (ii) to further the understanding of the syntactic phenomena discussed here, namely Differential Object Marking (henceforth, DOM) and Object Shift, by applying the theoretic assumptions of Generative Syntax to an Amazonian language. To this end, the first half focuses on some broad analyses of the language as a whole, while the second half explores the syntactic phenomena of Differential Object Marking and Object Shift in greater detail. The first chapter offers a general introduction to the dissertation. The second chapter presents some sociological and cultural aspects of the Tukano people and the linguistic family of Tukano, as well as a brief discussion about linguistic vitality, in order to highlight the relevance of works such as this one. The third chapter is about the phonology of the language, and discusses some basic structural issues of Tukano phonology, such as the phonemic inventory and the syllabic pattern, with special attention to tonal and stress phenomena. The fourth chapter analyzes the issue of DOM, using the Dependent Case Theory to explain the morphosyntactic behavior of DOM in Tukano. Specifically, the aforementioned chapter shows that only definite objects are marked with the accusative case marker {-re}, while indefinite objects remain unmarked in simple transitive constructions. In double object constructions, however, only the goal-dps are marked. The hypothesis postulated in chapter 4 is that {-re} marks the low dependent case (accusative) in the domain of the CP phase. Given that definite objects move out of the VP, whereas indefinite ones remain within the VP, only definite DPs trigger dependent case assignment in simple transitive constructions. In DOCs, on the other hand, only the goal-DP is in the same domain as the subject-DP, therefore only goal-DPs are {-re}-marked in DOCs. The fifth chapter investigates the same set of data using a different theoretical background, namely the phase-based analysis of Object Shift. The analysis presented in that chapter successfully explains the behavior of the morpheme {-re} in simple transitive constructions and DOCs, like the previous proposal made in chapter 4. However, the OS-based investigation also paves the way for an explanation of the occurrence of {-re} with topicalized XPs by postulating that the suffix {-re} has the grammatical role of marking definite non-focused elements that are merged in the edge of a phase: be it the CP or the v*P. Finally, the sixth chapter concludes the dissertation with a few closing remarks.